Implementing a Financial Management Curriculum With Survivors of IPV: Exploring Advocates' Experiences. (February 2016) - Silva-Martínez, Elithet; Stylianou, Amanda M.; Hoge, Gretchen L.; Plummer, Sara; McMahon, Sheila; Postmus, Judy L.
There is a clear need for financial literacy programs specific to survivors of intimate partner violence (IPV), as the skills and knowledge acquired during these programs stand to increase survivors' ability to achieve economic independence. In order to understand advocates' experiences in providing a financial literacy program, this study reports the findings of a qualitative study among 19 domestic violence advocates across 10 states. Findings revealed that advocates expressed complexities in providing financial literacy to survivors. Furthermore, advocates discussed the ways in which they incorporated the financial literacy curriculum into their own financial management behaviors. These findings provide critical information in regard to best practice approaches to incorporating financial literacy into IPV services.